Six new species of the Cyrtodactylus intermedius complex (Squamata: Gekkonidae) from the Cardamom Mountains and associated highlands of Southeast Asia - Murdoch, Matthew L.; Grismer, L. Lee; Wood, Perry L. Jr.; Neang, Thy; Poyarkov, Nikolay A.; Tri, Ngo Van; Nazarov, Roman A.; Aowphol, Anchalee; Pauwels, Olivier S.g.; Nguyen, Hung Ngoc; Grismer, Jesse L. (Zootaxa, 2019)
An integrative taxonomic analysis using color pattern, morphology, and 1449 base pairs of the ND2 mitochondrial gene and its five flanking tRNAs demonstrated that eight species-level lineages occur within the Cyrtodactylus intermedius complex (Cyrtodactylus intermedius sensu stricto, C. phuquocensis and related populations) of the Cardamom mountains and associated highlands that have a sequence divergence ranging 3.4–8.9%. Additionally, each lineage is discretely diagnosable from one another based on morphology and color pattern and most occur in specific geographic regions (upland areas, karst formations or islands) that prevent or greatly restrict interpopulation gene flow. Six of these lineages were masquerading under the nomen C. intermedius and are described as the following: Cyrtodactylus auralensis sp. nov. endemic to Phnom Aural, the highest mountain in Cambodia; C. bokorensis sp. nov. endemic to the Bokor Plateau, Cambodia; C. cardamomensis sp. nov. from the main block of the Cardamom mountains; C. thylacodactylus sp. nov. endemic to Phnom Dalai the northernmost peak of the Cardamom mountains; C. laangensis sp. nov. endemic to the Phnom Laang karst formation, Cambodia; and C. septimontium sp. nov. from the Bảy Núi Hills of southwest Vietnam.